2022
DOI: 10.1155/2022/7102736
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Factors in Cholangiocarcinoma Based on Integrated ceRNA Network Analysis

Abstract: This study is aimed at screening prognostic biomarkers in cholangiocarcinoma (CHOL) based on competitive endogenous RNA (ceRNA) regulatory network analysis. Microarray data for lncRNAs, mRNA, and miRNAs were downloaded from the GEO and TCGA databases. Differentially expressed RNAs (DERs) were identified in CHOL and normal liver tissue samples. WGCNA was used to identify disease-related gene modules. By integrating the information from the starBase and DIANA-LncBasev2 databases, we constructed a ceRNA network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These substrates can serve as potential biomarkers of LDHD deficiency, providing differential diagnostic criteria for D-lactic acidosis patients with LDHD mutations or with short bowel syndrome. In addition to D-lactic acidosis, down-regulation of LDHD expression is related to poor prognosis of many tumors such as cholangiocarcinoma and renal cell carcinoma 58 , 59 . Besides, elevated LDHD expression is found in prostate cancer cells, which exhibit higher mitochondrial D-lactate metabolism than normal cells 60 .…”
Section: Discussionmentioning
confidence: 99%
“…These substrates can serve as potential biomarkers of LDHD deficiency, providing differential diagnostic criteria for D-lactic acidosis patients with LDHD mutations or with short bowel syndrome. In addition to D-lactic acidosis, down-regulation of LDHD expression is related to poor prognosis of many tumors such as cholangiocarcinoma and renal cell carcinoma 58 , 59 . Besides, elevated LDHD expression is found in prostate cancer cells, which exhibit higher mitochondrial D-lactate metabolism than normal cells 60 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study highlighted the critical involvement of ELF4 in the cancer immune response ( 40 ). It has also been reported to be associated with immune cell infiltration and immune-related feature genes (CD14, CD163, CD33) in cholangiocarcinoma ( 41 ). Similarly, the present study revealed that ELF4 expression in ccRCC was closely related to the infiltration levels of multiple immune cell types compared with ELF3 and ELF5.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the DEmiRNAs and DElncRNAs was predicted using DIANA-LncBasev2 [ 18 , 19 ], and the correlation of DEmiRNAs and mRNA using starBase (Version 2.0) [ 20 ]. Subsequently, we retained the negative regulation among DEmiRNAs, DElncRNAs and mRNA.…”
Section: Methodsmentioning
confidence: 99%